Aging RNA granule dynamics in neurodegeneration - Rhine, Kevin; Al-Azzam, Norah; Yu, Tao; Yeo, Gene W. (Frontiers in Molecular Biosciences, 2022)
Disordered RNA-binding proteins and repetitive RNA sequences are the main genetic causes of several neurodegenerative diseases, including amyotrophic lateral sclerosis and Huntington’s disease. Importantly, these components also seed the formation of cytoplasmic liquid-like granules, like stress granules and P bodies. Emerging evidence demonstrates that healthy granules formed via liquid-liquid phase separation can mature into solid- or gel-like inclusions that persist within the cell. These solidified inclusions are a precursor to the aggregates identified in patients, demonstrating that dysregulation of RNA granule biology is an important component of neurodegeneration. Here, we review recent literature highlighting how RNA molecules seed proteinaceous granules, the mechanisms of healthy turnover of RNA granules in cells, which biophysical properties underly a transition to solid- or gel-like material states, and why persistent granules disrupt the cellular homeostasis of neurons. We also identify various methods that will illuminate the contributions of disordered proteins and RNAs to neurodegeneration in ongoing research efforts.